Professional teaching competence: key point of developing pupils’creativity (Journal of Educational Sciences, 2023)
The article points out the results of the research of a competent professional education specialistactivity aimed at developing creative abilities of trainees. In the modern multilingual education systemgreat importance is attached to teaching a foreign language, increasing students’ interest and motivatinglanguage learning. Through the use of active teaching methods that develop creativity, it is possible toactivate students and create a harmonious learning environment. The authors analyzed the concepts ofcompetence, creativity and conducted a survey on the use of innovative and creative teaching methodsby teachers. The survey involved 100 respondents: school teachers, graduate students, teachers of educationalcenters. More than 77% of respondents believe that it is necessary to use a creative approach inteaching foreign languages; more than 86.3% of respondents consider it is necessary to use critical thinkingmethods to increase the effectiveness of teaching foreign languages and develop creativity. It is crucialto prepare a creative environment for teaching foreign languages according to 86% of respondents.Respondents stated out methods as the most useful of specific methods: 73.3% chose “picture gallery”,of which 57.8% chose “quality line” and 53.3% chose the “mind mapping” option. In the final part ofthe survey, several methods were proposed to obtain information about the extent to which teachers usecritical thinking techniques.Key words: educational process, development of creative abilities, creativity, competency, pupils.